ANALISIS BIAYA DAN WAKTU PROYEK RENOVASI AREA PARKIR RSUD (RUMAH SAKIT UMUM DAERAH) SOREANG KABUPATEN BANDUNG - Royke Bahagia Rizka; Sephia Dwi Hidayat; Riki Setiawan (LPPM Politeknik Pajajaran ICB, 2022)
Abstract The parking area at the hospital is a permanent parking activity in providing adequate facilities for motorbikes, cars, ambulances, and goods trucks. The need for parking spaces that are actualized by the RSUD (District Public Hospital) Soreang Bandung Regency in accordance with the standard guidelines of the Directorate General of Land Transportation regarding parking space units, Hospitals with 197 TT, require 118 Parking space facilities (SRP), the design and planning of parking infrastructure in hospitals is very important because parking infrastructure and vehicle entrances take up a lot of land, for this reason, RSUD (District Public Hospital) Soreang Bandung Regency, carried out a parking area renovation project that aims to further improve visitor service and comfort. The renovation of the RSUD (District Public Hospital) Soreang Bandung Regency parking area was carried out by a third party / hospital parking building contractor. To analyze the cost and time of work, the researchers made a descriptive method by asking questions about current problems, so that the cost and time analysis was determined using the theory of Budget Cost Work Schedule (BCWS), Actual Cost Work Performance (ACWP), and Budget Cost Work Performance. (BCWP) and the use of the Earned Value concept in project performance assessment can be calculated various factors that indicate the progress and performance of project implementation, the results of research on cost efficiency and time effectiveness used by contractors in working on parking area renovation projects according to productivity and performance indices and cost projections and final project schedule using Critical Ratio (CR) = Schedule Performance Index (SPI) X Cost Performance Index (CPI) Keywords: Cirtical Ratio, Schedule Performance Index , Cost Performance Index, Budget Cost Work Schedul), Actual Cost Work Performance, Budget Cost Work Performance). Earned Value Concept